2022
DOI: 10.3390/brainsci12091125
|View full text |Cite
|
Sign up to set email alerts
|

The Remapping of Peripersonal Space in a Real but Not in a Virtual Environment

Abstract: One of the most surprising features of our brain is the fact that it is extremely plastic. Among the various plastic processes supported by our brain, there is the neural representation of the space surrounding our body, the peripersonal space (PPS). The effects of real-world tool use on the PPS are well known in cognitive neuroscience, but little is still known whether similar mechanisms also govern virtual tool use. To this purpose, the present study investigated the plasticity of the PPS before and after a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 67 publications
4
9
0
Order By: Relevance
“…If the direction of motion is crucial to the reshaping, one might have expected a constriction of the size of the PPS. Going back to the comparison between the present study with that of Ferroni et al [27], it is clear that the condition more similar across the two studies is the Hammer training, in which participants had "physical contact" with the targets but without moving the objects between the PPS and the EPS. Notably, in Ferroni et al [27] such training yielded a weak tendency to shrink the PPS, suggesting that the two kinds of training taken into account, might trigger similar PPS reshaping.…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations
“…If the direction of motion is crucial to the reshaping, one might have expected a constriction of the size of the PPS. Going back to the comparison between the present study with that of Ferroni et al [27], it is clear that the condition more similar across the two studies is the Hammer training, in which participants had "physical contact" with the targets but without moving the objects between the PPS and the EPS. Notably, in Ferroni et al [27] such training yielded a weak tendency to shrink the PPS, suggesting that the two kinds of training taken into account, might trigger similar PPS reshaping.…”
Section: Discussionsupporting
confidence: 49%
“…One of the key contributions of the present study is that it has successfully investigated PPS manipulations in a VR environment, as previous studies have questioned the possibility to do so. For instance, as mentioned in the Introduction, Ferroni et al [27] found that the same kind of training that triggered an expansion of PPS in a real life setting did not achieve the same result in VR, which prompted them to conclude that the PPS in VR might be characterized by different properties. One possible explanation to reconcile these ndings might be in terms of the differences between the experimental paradigm implemented here and in Ferroni et al [27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results raise intriguing questions about the limits and potential for virtual/augmented reality to mimic realness, and about whether awareness or belief that a stimulus is real is a necessary condition for performance differences (Banks et al, 2016). For example, the perception of reachable space surrounding the body can be extended, or “remapped,” following motor training with a real tool, but the same does not happen after motor training with a virtual reality tool (Ferroni et al, 2022). The effect of realness on memory advances various translational predictions, including that real objects may be preferable to pictures for facilitating learning and memory in the classroom (Strouse & Ganea, 2021), for maximizing sensitivity in neuropsychological evaluations (Beaucage et al, 2020; Hampstead et al, 2010), and perhaps for facilitating performance in individuals for whom memory function is disrupted due to brain injury (Sirigu et al, 1991), developmental disorder (Humphreys & Riddoch, 1999), natural aging (Tran et al, 2021), or neurodegenerative conditions (Clemenson & Stark, 2015).…”
Section: Discussionmentioning
confidence: 99%